DETERMINASI FINANCIAL DISTRESS PADA PERUSAHAAN PERTAMBANGAN PERIODE 2012-2016 - , SUPRAPTO; , HARIYATI (Jurnal Akuntansi AKUNESA, 2018)
The economic crisis that occurred in the United States in 2008, major impact on the world?s economy situation, especially in Indonesia. On of some sector that experienced a decline in the global export market is mining sector. This situation make a research about any factor that can affect financial distress in a firm is needed. This study aims to determine the effect of leverage, liquidity, firm size and profitability on financial distress. The total sample of this study was 37 companies. The results of this study indicate that leverage can affect positive financial distress. liquiditycan affect negative financial distress. profitability can affect negative financial distress. Keywords: Leverage, Liquidity, Firm Size, Profitability, And Financial Distress